2016
DOI: 10.3390/ma9030191
|View full text |Cite
|
Sign up to set email alerts
|

A Novel HA/β-TCP-Collagen Composite Enhanced New Bone Formation for Dental Extraction Socket Preservation in Beagle Dogs

Abstract: Past studies in humans have demonstrated horizontal and vertical bone loss after six months following tooth extraction. Many biomaterials have been developed to preserve bone volume after tooth extraction. Type I collagen serves as an excellent delivery system for growth factors and promotes angiogenesis. Calcium phosphate ceramics have also been investigated because their mineral chemistry resembles human bone. The aim of this study was to compare the performance of a novel bioresorbable purified fibrillar co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0
1

Year Published

2018
2018
2025
2025

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 43 publications
1
16
0
1
Order By: Relevance
“…Alveolar bone contraction following tooth extraction has been demonstrated in various studies [1][2][3]. To counteract this ridge resorption, biphasic bone graft materials has been investigated for ridge preservation [20,21]. The positive effect of non-crosslinked collagen membrane in ridge preservation was also demonstrated in the previous study [15].…”
Section: Discussionmentioning
confidence: 98%
“…Alveolar bone contraction following tooth extraction has been demonstrated in various studies [1][2][3]. To counteract this ridge resorption, biphasic bone graft materials has been investigated for ridge preservation [20,21]. The positive effect of non-crosslinked collagen membrane in ridge preservation was also demonstrated in the previous study [15].…”
Section: Discussionmentioning
confidence: 98%
“…Although studies in dogs, minipigs, sheep, and non-human primates, could provide a better insight into new bone formation and scaffold effectiveness thanks to the closer resemblance to the human bone, only studies employing rat and rabbit models were found to satisfy eligibility criteria, and were, therefore, included in the present systematic review [21,[27][28][29]126]. Even though after the first step of screening, studies in dogs, sheep, and pigs were included, the full-text analysis revealed that most of these studies did not meet the selection criteria due to a reduced sample size (n < 6 animals per group) or the non-critical dimensions of the bone defects [94,100,102,103,106]. Among the papers included, the most frequently used CSD model was the CSD in rat calvaria, which is one of the most commonly used animal models for evaluating bone healing [23,127].…”
Section: Discussionmentioning
confidence: 99%
“…A commercialized cell, human osteosarcoma (MG-63, ATCC CRL-1427) osteoblast-like cell, was used for the cell test in this study. The cell has been used for testing the bioactivity and biocompatibility of various biomaterials [ 24 , 25 , 26 ]. MG-63 cells were cultured in Dulbecco’s Modified Eagle’s Medium (DMEM) medium containing 10% heat-inactivated Fetal bovine serum (FBS), 50 U/mL penicillin, and 50 mg/mL streptomycin on a culture dish in a humidified atmosphere of 5% CO 2 and 95% air at 37 °C.…”
Section: Methodsmentioning
confidence: 99%